Comic Books, Graphic Novels and the Holocaust: Beyond Maus, Ewa Stańczyk (ed.) (2019). Issue 2 (1st November 2020) - Precup, Mihaela
Review of: Comic Books, Graphic Novels and the Holocaust: Beyond Maus, Ewa Stańczyk (ed.) (2019)Abingdon and New York: Routledge, 142 pp., ISBN 978-1-13859-864-5, h/bk, £96.00, p/bk, £29.59